2009
DOI: 10.1179/174328109x445714
|View full text |Cite
|
Sign up to set email alerts
|

A study of shell growth irregularities in continuously cast 310S stainless steel

Abstract: Growth irregularities in continuous casting are believed to be associated with crack formation and breakouts. Differential thermal analysis on 310S stainless steel samples indicated primary precipitations of both austenite and ferrite during solidification. In tensile tests on solidifying samples, abrupt shrinkages in volume were detected in the peritectic range of temperatures. Micrographic and microsegregation analysis on samples extracted from a breakout shell revealed high ratios of primary-precipitated au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…For steels, the solidification process during continuous casting, especially the structural evolution in high temperature, plays a crucial role in the quality of the slabs. Once the alloy content locates in the peritectic range, the volume shrinkage and elastic straining will occur during the initial solidification within the mould, which affects the high-temperature hot ductility, leading to issues such as poor surface quality, cracks and even breakout [3,4]. In the case of the primary solidification to austenite, the hot workability of stainless steel is worse due to the interphase segregation and the accumulation of inclusions [5].…”
Section: Introductionmentioning
confidence: 99%
“…For steels, the solidification process during continuous casting, especially the structural evolution in high temperature, plays a crucial role in the quality of the slabs. Once the alloy content locates in the peritectic range, the volume shrinkage and elastic straining will occur during the initial solidification within the mould, which affects the high-temperature hot ductility, leading to issues such as poor surface quality, cracks and even breakout [3,4]. In the case of the primary solidification to austenite, the hot workability of stainless steel is worse due to the interphase segregation and the accumulation of inclusions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several improved models of different heat transfer and solidification phenomena have been developed. El-Bealy [9], extended the fluctuation macrosegregation technique to simulate mold heat transfer phenomena in addition to the microstructure evolution [5] [10]. The comparison between these phenomena reveals that the fluctuated macrosegregation technique is more accurate than the use of microstructure evolution technique.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison between these phenomena reveals that the fluctuated macrosegregation technique is more accurate than the use of microstructure evolution technique. Nassar et al [10], studied the growth irregularities during continuous casting caused by local variations in surface temperature due to the solidification behavior of 310S stainless steel. They concluded that large variations in the surface temperature were expected due to the variation in heat extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the new application of ultrathick slab casters, the flow pattern and heat transfer mechanism in the mould have as yet not been investigated completely. Most of the previous works [7][8][9][10][11] developed both experimental and numerical models for the analysis of flow behaviour and solidified shell distribution. However, those models w'ere confined to conventional geometry, in which the maximum thickness was ,300 mm, such as billet, bloom and slab.…”
Section: Introductionmentioning
confidence: 99%